Theory of Planned Behaviour in Marketing: Cognitive Consideration on Purchase Decision - Sari, Ovi Hamidah (Manunggal Halim Jaya, 2022)
The desire to search for products sequentially is dominated by the gifts or rewards offered and the costs of searching for a product itself. A person's cognitive ability will affect when they stop searching for a product until they decide to buy without remembering. Advances in computerized technology that are more intensive, like today's purchase decisions, will be faster and better. Cognitive intelligence and preferences as well as long-term memory in superior decision making, if applied, will successfully avoid negative purchase decision results, where consumers who have good numeracy skills will produce more explicit mental representations; this process can be necessary for superior decision making. Resume of prior research in this study use 13 of manuscript form scopus databased index in year 2017 - 2021. The proposition in this mapping is Correlation Theory of planned behavior theory in the aspect of the field of management (e.g., marketing, Technology, Marketing, E-Commerce) make a positive contribution as a grounded theory to explain the variable antecedent and also its correlation to other theories.